Investigating the Drought and Salinity Effect on the Redox Components of Sulla coronaria (L.) Medik - Silvia De Rossi; Gabriele Di Marco; Laura Bruno; Angelo Gismondi; Antonella Canini (MDPI AG, 2021)
For the Mediterranean region, climate models predict an acceleration of desertification processes, thus threatening agriculture. The present work aimed to investigate the effect of drought and salinity on Sulla coronaria (L.) Medik., a Mediterranean forage legume, for understanding plant defence systems activated by these stressors. In detail, we focused our attention on the variations on the plant redox status. Plants were subjected to suboptimal watering and irrigation with sodium chloride (NaCl) solutions. The same salt treatment was applied for in vitro tests on seedlings. Water content did not change after treatments. Salt negatively influenced seed germination and seedling development, but it did not affect photosynthesis parameters, contrary to what was observed in adult plants. Proline concentration increased in all samples, while abscisic acid level increased exclusively in seedlings. NaCl caused accumulation of superoxide anion in plants and seedlings and hydrogen peroxide only in seedlings; nevertheless, lipid peroxidation was not detected. Total phenolics, glutathione, expression level, and activity of antioxidant enzymes were assayed, revealing a complex antiradical molecular response, depending on the type of stress and development stage. Our results confirm Sulla as a drought- and salt-tolerant species and highlight its ability to counteract oxidative stress. This evidence suggests a key role for the redox components, as signal transduction messengers, in Sulla acclimation to desertification. Finally, plants and seedlings showed different acclimation capacity to salinity, revealing a greater genomic plasticity for seedlings.